2015
DOI: 10.1021/jp510949x
|View full text |Cite
|
Sign up to set email alerts
|

Energy Dependence of the Ruthenium(II)-Bipyridine Metal-to-Ligand-Charge-Transfer Excited State Radiative Lifetimes: Effects of ππ*(bipyridine) Mixing

Abstract: The variations in band shape with excited state energy found for the triplet metal to ligand charge transfer ((3)MLCT) emission spectra of ruthenium-bipyridine (Ru-bpy) chromophores at 77 K have been postulated to arise from excited state/excited state configurational mixing. This issue is more critically examined through the determination of the excited state energy dependence of the radiative rate constants (kRAD) for these emissions. Experimental values for kRAD were determined relative to known literature … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

6
89
3

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 18 publications
(98 citation statements)
references
References 81 publications
6
89
3
Order By: Relevance
“…[7][8][9][10][11][12][13][14] In organometallic LEDs, for instance, the interaction between the singlet metal-to-ligand charge transfer ( 1 MLCT) and the lowest triplet metal-to-ligand charge transfer ( 3 MLCT) states leads to robust ISC, resulting in high phosphorescence quantum yield. [15][16] To date, many phosphorescent molecules are either organometallic molecules or organic molecules with halogen atoms. [17][18] Such dominance has two causes, both well-documented.…”
Section: Toc Graphicmentioning
confidence: 99%
See 1 more Smart Citation
“…[7][8][9][10][11][12][13][14] In organometallic LEDs, for instance, the interaction between the singlet metal-to-ligand charge transfer ( 1 MLCT) and the lowest triplet metal-to-ligand charge transfer ( 3 MLCT) states leads to robust ISC, resulting in high phosphorescence quantum yield. [15][16] To date, many phosphorescent molecules are either organometallic molecules or organic molecules with halogen atoms. [17][18] Such dominance has two causes, both well-documented.…”
Section: Toc Graphicmentioning
confidence: 99%
“…Molecular phosphorescence has a high potential in information processing applications, including sensors, biological imaging, and LEDs, which has promoted a vivid search for efficient, low-cost, and environment-friendly phosphorescent materials. Naturally, a crucial point in this search is to develop molecules with efficient intersystem crossing (ISC), the nonradiative transition between electronic states with different spin multiplicity. In organometallic LEDs, for instance, the interaction between the singlet metal-to-ligand charge transfer ( 1 MLCT) and the lowest triplet metal-to-ligand charge transfer ( 3 MLCT) states leads to robust ISC, resulting in high phosphorescence quantum yield. , …”
mentioning
confidence: 99%
“…These observations suggest a basis for selecting Ru photosensitizers with lower energy 3 MLCT than 3 MC excited states: the 77 K MLCT emission maximum of the sensitizer should have a lower energy than the energy for breaking both Ru−ligand bonds along the weakest bonding axis. 21 The point for [Ru(bpy) 3 ] 2+ is based on 3 MC calculations reported by Sun et al, 15 and 77 K emission spectra reported by Thomas et al 21 The code numbers in panel A are from The Supporting Information is available free of charge on the…”
Section: ■ Conclusionmentioning
confidence: 99%
“…The chemistry of transition-metal hydride clusters has recently received significant interest. [1,2] Such compounds play a key role as intermediates in several homogeneous and heterogeneous catalyses [3] with significant contributions in hydrogen storage. [4] Importantly, copper hydride chemistry has evolved towards the design of nanosized ligand-protected polyhydrido copper clusters that have emerged as a new class of materials in the field of nanoscience, owing to their various potential applications.…”
mentioning
confidence: 99%
“…Received: ((will be filled in by the editorial staff)) Revised: ((will be filled in by the editorial staff)) Published online: ((will be filled in by the editorial staff)) ), Triethylamine and phenylacetylene were prepared as described in the literature. [1][2][3] Solvents were purified following standard protocols. Melting points were measured by using a Fargo MP-2D melting point apparatus.…”
mentioning
confidence: 99%